Effects of alfalfa hay by rhodes hay replacement in horses performance - Manzano, Airton; Novaes, Nelson José; Carvalho, Roberto T. Losito de (Pesquisa Agropecuaria Brasileira, 2014)
These experiments were carried out in order to replace totally or partially alfalfa hay (Medicago sativa L.) by Rhodes hay (Chloris gayana, Kunth), during 70 days of equine feeding. The work was done on 24 growing females, being twelve Arabian and twelve Manga-larga, that in the average were 20-month old and weighing 276 kg. Three block designs of eight animals each were selected at randon according to their weight, age and breed, to compare the different feed blend. The feed blends were the following: 60% concentrate and 40% Rhodes hay (R1), 60% concentrate, 20% Rhodes hay and 20% alfalfa hay (R2), and 60% concentrate and 40% alfalfa hay (R3). The concentrate with about 20% protein was made up of 40% cottonseed meal, 40% corn ear and 20% wheet bran. The animals were daily fed at 8 a.m. with 1/2 concentrate, at 1 p.m. with 1/2 concentrate and 1/3 hay, and at 5 p.m. with the remainder 2/3 hay. The average daily weight gain, daily intake on a dry matter basis and feed conversion were respectively: 0.446 kg, 8.976 kg, 21.402kg for R1, 0.509 kg, 9.032 kg, 19.518 for R2, and 0.659 kg , 0.329 kg, 12.855 for R3. Although the results were in favor of feed blend R3 (P<0,01) for weight gain, the economical analysis shows that Rhodes hay can replace alfalfa hay.